PENGARUH MEDIA POP-UP BOOK TERHADAP HASIL BELAJAR MATERI BANGUN RUANG SISWA KELAS IV SEKOLAH DASAR - Anwar, Muhammad Syaiful; Winarti, Puji; Sarwono, Ridha (Universitas Tanjungpura, 2025)
This study was motivated by the observation that fourth-grade students exhibited relatively low learning outcomes, which were caused by students still experiencing difficulties in understanding the abstract concepts of solid geometry. Furthermore, students tended to perceive mathematics as a difficult subject, and there was a lack of motivation in the context of mathematics learning. The primary purpose of this research was to determine whether the implementation of pop-up book media has a significant effect on students’ learning outcomes in solid geometry. This study employed a quantitative research approach using a quasi-experimental method with a nonequivalent control group design. The sampling technique applied was saturated sampling, in which the entire population of 43 students was selected as the sample. The researcher employed a multiple-choice test comprising 25 items, which had been previously assessed for validity and reliability. Data analysis techniques included tests for normality, homogeneity, correlation, and hypothesis testing using IBM SPSS Statistics 27 and Microsoft Excel 2019. The findings of the analysis reveal that implementing pop-up book media in teaching three-dimensional shapes to fourth-grade students during the 2024/2025 academic year significantly enhances their learning outcomes. This conclusion is further substantiated by the results of the t-tes, which show a biserial correlation coefficient of r_b= 0,7895 and a calculated t_value of 8.2372, which exceeds the t_table value of of 2.021 (8.2372 > 2.021). Therefore, It can be inferred that the implementation of pop-up book media has a significant effect on the learning outcomes of fourth-grade students in studying three-dimensional shapes at SD N Wiru 03, Bringin District, Semarang Regency.